Comenius’ Ethical Visions of the Improvement of Human Things - Somr, Miroslav; Pavličiková, Helena (Wydawnictwo Naukowe UAM, 2015)
The paradox about the Reformation is that, rather than consolidating European Christendom, it contributed to deepening the rifts between Catholics and Protestants as well as Lutherans and Calvinists, bringing about religious and civil strife. Comenius got involved in the antagonistic circumstances through his political philosophy, aspiring to weeding out the causes of hatred and mutual disagreement. This abiding endeavour of his achieved prominence in Panorthosia (Universal Improvement), which renders his best vision of permanent reconciliation resting upon educational, religious and civil reforms. Comenius’ ethical pursuit of improving human matters is rooted in his philosophical thought regarding man as an individual whose purpose in this world is to be humane: wise, moral and pious.
Wizje etyczne Comeniusa o doskonaleniu człowieczeństwa
Keywords: Protestantismism; stoicism; chiliasm; pansophia; pampaedia; political philosophy; political conservatism; Eruditio; Religio; Politica; Panorthosia